Herbs in Mongolia - Narangerel, Tuya; Mańkowska, Dorota (Biotechnology and Food Science, 2019)
Herbal plants have been an extremely important part of Mongolian medicine for centuries. They constitute an equally important group of drugs as synthetic drugs and are widely use in both prophylaxis and therapy of various types of diseases. Despite the rich history of the use of Mongolian herbs, many of them have still not been studied. Moreover the knowledge about many species, even the most commonly used, remains unknown to scientists. This review presents both a historical and geographical outline of Mongolian herbal medicine as well as the most popular species of herbs, their systematic, chemical composition and usage.